WLAV based state estimation of power system using pseudo-voltage measurements - Rakpenthai,C. (2015)
© 2014 IEEE. This paper presents a new power system state estimation method based on pseudo-measurements. The conventional and synchronizing phasor measurements are employed to calculate the pseudo-measurements of voltage and current phasors. Using pseudo-measurement, the measurement matrix which describes relations between measurements and state variables contains only 0 or 1. In this work, the state estimation problem is formulated based on the weighted least absolute value (WLAV) criteria. The solutions are obtained by an interior point method considering equality and inequality constraints. Comparisons with the conventional hybrid method are also performed on the IEEE 14-bus system in the presence of bad data. Results indicate that the proposed method can provide accurate solutions but with smaller computation time.